2022
DOI: 10.1111/liv.15481
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentration of taurochenodeoxycholic acid predicts clinically significant portal hypertension

Abstract: Background & Aims: Severity of portal hypertension is usually quantified by measuring the hepatic venous pressure gradient (HVPG). However, due to its invasiveness, alternative markers are being sought. Bile acids (BA), being synthesized, metabolized, and transported by the liver, seem to have the potential to serve as endogenous markers. The aim of the present study was to determine whether serum BA reflect the severity of portal hypertension. Methods:We correlated serum concentrations of individual BA with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…A correlation between serum levels of GCDCA and M2BPGi, a non-invasive marker for hepatic fibrosis, was observed in patients with biliary atresia. In a recent report, serum levels of GCDCA and TCDCA were significantly correlated with portal pressure and showed a high potential to predict clinically significant portal hypertension in adults with cirrhosis 8 . In the early stages of cholestasis and cirrhosis, GCDCA was relatively higher than TCDCA 7 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A correlation between serum levels of GCDCA and M2BPGi, a non-invasive marker for hepatic fibrosis, was observed in patients with biliary atresia. In a recent report, serum levels of GCDCA and TCDCA were significantly correlated with portal pressure and showed a high potential to predict clinically significant portal hypertension in adults with cirrhosis 8 . In the early stages of cholestasis and cirrhosis, GCDCA was relatively higher than TCDCA 7 .…”
Section: Discussionmentioning
confidence: 94%
“…To determine why bile acid itself may be a long-term prognostic marker and its potential role in the mechanism of liver injury in biliary atresia, a comprehensive examination of bile acid compositions in long-term native liver survivors is required. The validation of bile acid profiles in adults with cirrhosis has demonstrated a strong correlation between 6-month mortality, portal hypertension and bile acid compositions, such as glycochenodeoxycholic acid (GCDCA) or taurochenodeoxycholic acid (TCDCA) 7 , 8 . In the validation of bile acid profiles in biliary atresia, it is crucial to focus on cases that meet the following criteria: (1) achieving normalized bilirubin levels to eliminate the impact of cholestasis on bile acid compositions and (2) studying cases in which physiological changes in bile acids have been completed, typically involving individuals aged 11 years and older 9 .…”
Section: Introductionmentioning
confidence: 99%
“…33 TCA and TCDCA participate in histamine release, affect PGE2 content, and thus participate in inflammatory responses. 34,35 DCA is also associated with the production of pro-inflammatory cytokines. 36 Previous studies have shown that UDCA can relax blood vessels, lower blood lipids, and prevent thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, assessment of cACLD is an essential part of the evaluation of chronic liver disease patients in order to prognosticate, stratify therapeutic and surveillance strategies 8 . Research showed that elevated serum BA concentrations have been shown to be a more sensitive test for the detection of liver cirrhosis than conventional liver function tests 14 . Therefore, this study developed two different models (RF and SVM) based on individual BA profiles of serum samples to recognize cACLD in patients with HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, bile acid (BA), endogenous compounds that undergo efficient enterohepatic circulation, have been confirmed as an important factor in the pathophysiology of the dynamic component of portal hypertension in both animal models and in humans 14 , 15 . Therefore, the aim of our study was to develop prediction model based on individual BA profiles of serum samples to identify cACLD in patients with HBV infection.…”
Section: Introductionmentioning
confidence: 99%